The Life and Times of Gerald de Cruz : A Singaporean of Many Worlds - Asad Latif (Book collections on Project MUSE., 2015)
Gerald de Cruz's life overlapped many of the spheres of Singapore's history after World War II. As a Eurasian, a nationalist, a communist and then a democratic socialist, as a journalist and a writer, he represents the insurgent energies of a truculent time when a nascent nation was seeking the basis of statehood. His commitment to progressive ideas and movements reveals a man of integrity in search of himself in a better world. This book seeks to portray his place in time, particularly for younger Singaporeans who did not live in an era that has inaugurated the history of independent Singapore.